Social Criticism, Inmanent critique and Trascendental Critique The question of Inmanent Critique in Critical Theory - Caviglia Marconi, Alessandro (2017)
The present work seeks to clarify the issue of immanent criticism and transcendent criticism in the so-called Critical Theory. To this end, the different forms of social criticism are used to present clearly what the Frankfurt School calls “immanent criticism of society”, following in the footsteps of Hegel and Kant. After that, it presents the observations that Rainer Forst, reinserting a Kantian inspiration, presents a distinction between immanent criticism / transcendent criticism.